Elevated circulating follistatin associates with an increased risk of type 2 diabetes - Chuanyan Wu (Nature Portfolio, 2021)
Follistatin promotes in type 2 diabetes (T2D) pathogenesis in model animals and is elevated in patients with T2D. Here the authors report that plasma follistatin associates with increased risk of incident T2D in two longitudinal cohorts, and show that follistatin regulates insulin-induced suppression lipolysis in cultured human adipocytes.